2022
DOI: 10.15741/revbio.09.e1176
|View full text |Cite
|
Sign up to set email alerts
|

First record of Cymatodiscus planetophorus (Bacillariophyta) for littorals of NW Mexico; ecological remarks

Abstract: Este archivo PDF es un manuscrito no editado que ha sido aceptado para publicación. Esto es parte de un servicio de Revista Bio Ciencias para proveer a los autores de una versión rápida del manuscrito. Sin embargo, el manuscrito ingresará a proceso de edición y corrección de estilo antes de publicar la versión final. Por favor note que la versión actual puede contener errores de forma. Primer registro de Cymatodiscus planetophorus para litorales del noroeste de México y observaciones ecológicasFirst record of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…parvum, and F. doliolus have been interpreted in La Paz, to reflect an incursion of tropical/subtropical water during anomalously warm periods (Acevedo-Acosta et al, 2021). Also, the rapid increase up to ~7.4% of the C. planetophorus (Figure 4), a tropical taxon commonly found at temperatures above 23.3°C in the northwestern coasts of Mexico (Estrada Gutiérrez et al, 2022), supports the idea that warmer conditions prevailed during this period. Diatom sedimentary records (Barron and Bukry, 2007;Barron et al, 2013;Esparza-Alvarez et al, 2007;Martinez -Lopez et al, 2007) and planktonic foraminifera (Field et al, 2006) from the Eastern North Pacific also showed evidence of the global warming trend.…”
Section: Current Warm Period (Zone IV ~1920 Ce To ~Today)mentioning
confidence: 60%
See 1 more Smart Citation
“…parvum, and F. doliolus have been interpreted in La Paz, to reflect an incursion of tropical/subtropical water during anomalously warm periods (Acevedo-Acosta et al, 2021). Also, the rapid increase up to ~7.4% of the C. planetophorus (Figure 4), a tropical taxon commonly found at temperatures above 23.3°C in the northwestern coasts of Mexico (Estrada Gutiérrez et al, 2022), supports the idea that warmer conditions prevailed during this period. Diatom sedimentary records (Barron and Bukry, 2007;Barron et al, 2013;Esparza-Alvarez et al, 2007;Martinez -Lopez et al, 2007) and planktonic foraminifera (Field et al, 2006) from the Eastern North Pacific also showed evidence of the global warming trend.…”
Section: Current Warm Period (Zone IV ~1920 Ce To ~Today)mentioning
confidence: 60%
“…In the California Current System and the Eastern Equatorial Pacific, during warm and low productivity conditions, diatom assemblages are composed of one or more of the following species: F. doliolus , T. oestrupii , N. interruptestriata (Barron et al, 2010, 2013; Lange et al, 1987, 1990; Romero et al, 2011; Sancetta, 1992, 1995; Sautter and Sancetta, 1992; Schrader et al, 1993), T. bacillare (Baumgartner et al, 1985), T. nitzschioides var. parvum (Romero et al, 2011), T. lineata, R. bergonii (Baumgartner et al, 1985; Kemp et al, 2000; Lange et al, 1987), C. litoralis (Barron and Bukry, 2007; Barron et al, 2004, 2005; Sancetta, 1995), C. planetophorus (Estrada Gutiérrez et al, 2022), N. pelagica (Almaraz-Ruiz, 2017), and other taxa in minor amounts. In particular, R. bergoni is a deep-dwelling taxon (up to ∼ 130 m, Kemp et al, 2000) that indicates strong stratification in the water column in tropical to subtropical regions (Baumgartner et al, 1985; Kemp et al, 2000; Lange et al, 1987, 1994; Romero et al, 2011).…”
Section: Resultsmentioning
confidence: 99%